Penerapan Algoritma SVM pada Software Define Network untuk Mendeteksi dan Mitigasi Serangan DDOS pada Server Jaringan - andi purnomo; Avrijsto Amandri Achyar (FORMAT, 2025)
Software Defined Network (SDN) is a network architecture that is very useful in the future where SDN can be used to manage network traffic on server networks. SDN can be implemented using a variety of controllers. In the controller the developer can configure it with various algorithms or other functions. At present, cyber crimes are increasingly numerous and dangerous. One of the most dangerous cyber attacks that is mostly carried out by both novice and professional hackers is the DDoS attack. DDoS attacks are aimed at crippling servers with server administration with multiple streams and packets. SDN as an architect for managing networks can be used to detect and counteract DDoS attacks so that servers are protected from these attacks. In this study researchers used SDN configured using the SVM algorithm to detect and mitigate DDOS attacks. In this study, the researchers obtained results where SDN with the SVM algorithm configuration obtained an accuracy rate of 99.67%. The SDN speed configured with the SVM algorithm does not exceed 0.30ms. Wireshark statistics show that SDN with the SVM algorithm configuration can stabilize and mitigate packets detected as DDOS.